Knowledge of Health Consequences of Psychoactive Substance Use among Senior Secondary School Students (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The rate of psychoactive substance (PAS) use in the adolescent group is increasing around the world. Drug abuse has a negative impact on students’ education especially that of secondary school students. This study aimed to assess the prevalence of psychoactive substance use and knowledge of the health consequences among secondary school students in Ogun State, Nigeria. A cross-sectional study was carried out among 528 consenting students selected using random sampling method. Data obtained using a validated modified World Health Organization’s guidelines questionnaire were analyzed with SPSS 20, p-Value ≤ 0.05 was considered significant. Majority (78.8%) were within the age group 15-18 years, males were 61.4%. Alcohol (95.0%) ranked first of all the substances been consumed among the current PAS users. Age was highly significantly associated with PAS use. Average knowledge of health consequences of PAS use was 11.5%. There is need for continuous health educational intervention to boost the respondents’ knowledge about health consequences of uses of psychoactive substances.Dhaka Univ. J. Pharm. Sci. 19(2): 199-205, 2020 (December)